A NOTE ON RESOLVENT CONVERGENCE ON A THIN DOMAIN - Silva, Ricardo P. (Cambridge University Press, 2014)
In this paper we provide a new proof of strong convergence of resolvent operators associated with boundary value problems on thin domains.
Keywords: thin domains; resolvent convergence